Noonan, Benjamin J. Advances in the Study of Biblical Hebrew and Aramaic: New Insights for Reading the Old Testament. Grand Rapids, Michigan: Zondervan, 2020. 268p. ISBN 978-0-310-59601-1. - Galvão, Eloá Moura (Vox Scripturae - Revista Teológica Internacional, 2025)
Reseña del libro "Noonan, Benjamin J. Advances in the Study of Biblical Hebrew and Aramaic: New Insights for Reading the Old Testament. Grand Rapids, Michigan: Zondervan, 2020. 268 págs. ISBN 978-0-310-59601-1."